The American Sign Language handshape starter : a beginner's guide - Tennant, Richard A. (Clerc Books/Gallaudet University Press, 2002)
Contains illustrations of over 1,600 hand signs used in American Sign Language, with their English meanings, including one-hand and two-hand signs; grouped by initial handshape. Includes an alphabetical index of English words, with a page indication of the related illustration.